2008
DOI: 10.1016/j.juro.2008.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guided Percutaneous Microwave Ablation for Small Renal Cancer: Initial Experience

Abstract: Ultrasound guided percutaneous microwave ablation appears to be a safe and effective technique for small renal cell cancer in select patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 22 publications
2
79
0
Order By: Relevance
“…MWA is a minimally invasive technique that has been already used to treat benign and malignant tumors [78][79][80]. Nevertheless, only a few studies considering MWA efficacy in the treatment of benign solid thyroid nodules are available.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…MWA is a minimally invasive technique that has been already used to treat benign and malignant tumors [78][79][80]. Nevertheless, only a few studies considering MWA efficacy in the treatment of benign solid thyroid nodules are available.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Use of microwave ablation has been studied extensively in the liver, but remains limited for the kidney. Actually, the literature supports the use of MWA for the treatment of small renal tumors with rare objections [7,[29][30][31]. This technology can be applied in selected patients who are not candidates for surgery, as an alternative to other ablative techniques [11,[29][30][31].…”
Section: Resultsmentioning
confidence: 98%
“…Actually, the literature supports the use of MWA for the treatment of small renal tumors with rare objections [7,[29][30][31]. This technology can be applied in selected patients who are not candidates for surgery, as an alternative to other ablative techniques [11,[29][30][31]. Though MWA achieved comparable results to those obtained with RF ablation or cryoablation, MWA needs a relatively short ablation time and may be more suitable for patients with a variety of comorbidities who cannot tolerate long-time anesthesia [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clark et al (9) demonstrated the feasibility of MWTA in 10 patients with large kidney tumors before radical nephrectomy and demonstrated complete tumor cell kill inside the ablated lesions. Liang et al (17) confirmed the efficacy of MWTA on renal tumors by treating 12 patients with small lesions (<4 cm in diameter) and no evidence of recurrence after 20 months of follow-up, while Castle et al (18) reported poor oncologic outcomes and significant complication rates in a series of 10 patients with tumor diameter size ranging from 2.0 to 5.5 cm treated by laparoscopic-or CT-guided percutaneous MWTA. Rational explanations for such similar discrepancies could be easily found by evaluating either the absence of a standardized and reproducible method for microwave administration or the adequate selection of patients.…”
Section: Discussionmentioning
confidence: 93%